Process of a new dramaturgy from "The Bread Shop" by Bertolt Brecht. (The Voz a Vos Bulletin, 2021)
Brecht's theater is still current and, to analyze it, it is necessary to put it in its own historical context and draw conclusions for our time. In this presentation, we are going to discuss the process of dramaturgical creation based on the Brechtian text “The Breadstore”. As a first step, we are going to present it within the historical context in which it was written, in Germany 1930, just before the Nazis took power. Then, we will discuss some fundamental points of Brecht's dramaturgy, such as his working methods, the function of the fable in his dramaturgy, and the dialectical conception of the text. In a second moment, we will present our work methodology and what we have achieved so far.